Glial overexpression of Dube3a causes seizures and synaptic impairments in Drosophila concomitant with down regulation of the Na(+)/K(+) pump ATP?. - Hope, K.A.; LeDoux, M.S.; Reiter, L.T. (Neurobiology of Disease, 2017)
Duplication 15q syndrome (Dup15q) is an autism-associated disorder co-incident with high rates of pediatric epilepsy. Additional copies of the E3 ubiquitin ligase UBE3A are thought to cause Dup15q phenotypes, yet models overexpressing UBE3A in neurons have not recapitulated the epilepsy phenotype. We show that Drosophila endogenously expresses Dube3a (fly UBE3A homolog) in glial cells and neurons, prompting an investigation into the consequences of glial Dube3a overexpression. Here we expand on previous work showing that the Na(+)/K(+) pump ATP? is a direct ubiquitin ligase substrate of Dube3a. A robust seizure-like phenotype was observed in flies overexpressing Dube3a in glial cells, but not neurons. Glial-specific knockdown of ATP? also produced seizure-like behavior, and this phenotype was rescued by simultaneously overexpressing ATP? and Dube3a in glia. Our data provides the basis of a paradigm shift in Dup15q research given that clinical phenotypes have long been assumed to be due to neuronal UBE3A overexpression.